Innovative green HPTLC strategy for the analysis of telmisartan–nebivolol combination used for hypertension control. Application to dosage form and biological fluids - Sayed M. Derayea; Mahmoud Abdelgaleel; Dalia M. Nagi; Ebtihal Samir (Sustainable Chemistry and Pharmacy, 2026)

Facile one-pot green chemistry approach with whiteness assessment for unveiling micellar-mediated fluorescence amplification of midodrine: A comprehensive study of analytical significance - Pakinaz Y. Khashaba; Mahmoud Abdelgaleel; Dalia M. Nagi; Mohamed Oraby; Sayed M. Derayea (Sustainable Chemistry and Pharmacy, 2025)

Spectrofluorimetric Protocol for Estimation of Commonly Used Antispasmodic Drotaverine. Fluorescence Quenching Study - Sayed M. Derayea; Nihad A. Mahmoud; Deena A. M. Noureldeen; Tamer Z. Attia (Journal of Fluorescence, 2024)
A fast, simple, accurate, precise, and cheap fluorimetric protocol has been proposed for analysis of a phosphodiesterase-IV inhibitor, namely drotaverine hydrochloride. Fluorimetric protocol is based on estimating the decrease in the eosin Y fluorescence intensity by quantitative addition of drotaverine at pH 3.1 (acetate buffer). An ion pair complex is formed, which leads to quenching in the fluorescence intensity of the dye without need of prior extraction at 534 nm (λ ex . 339 nm). Different reaction perimeters which influence the production of complex (ion pair between drotaverine and eosin) were deeply investigated and optimized. The developed fluorimetric protocol is capable for quantitative estimation of drotaverine in linear range of 0.4 to 2.5 µg mL −1 . After method validation in respect to ICH guidelines, it was applied to determine drotaverine in its commercial preparation. By comparing with other reported method, the developed and validated fluorimetric protocol is capable for estimation of drotaverine in commercial preparation with good accuracy and excellent precision.

Integration of sustainable chemistry frameworks with a single-pot, on-off fluorescence approach for enabling the facile quantification of mosapride; Application to pharmaceutical tablets and content uniformity - Sayed M. Derayea; Fatma F. Mohammed; Ahmed A. Hamad; Khalid M. Badr El-Din (Sustainable Chemistry and Pharmacy, 2024)

Selectivity Improvement for Spectrofluorimetric Determination of Oseltamivir Phosphate in Human Plasma and in the Presence of Its Degradation Product - Mahmoud A. Omar; Sayed M. Derayea; Islam M. Mostafa (Journal of Fluorescence, 2017)

Selective Spectrofluorimetric Method with Enhanced Sensitivity for Determination of Silodosine in Dosage Form and Human Plasma. Application to Stability Studies and Content Uniformity Testing - Mahmoud A. Omar; Abdel-Maaboud I. Mohamed; Sayed M. Derayea; Mohamed A. Hammad; Abobakr A. Mohamed (Journal of Fluorescence, 2017)